Development of angiosarcoma in a mediastinal non‐seminomatous germ cell tumor that exhibited growing teratoma syndrome during chemotherapy. Issue 1 (8th November 2018) - Matsuoka, Shunichiro; Koyama, Tsutomu; Takeda, Tetsu; Yamada, Kyoko; Hyogotani, Akira; Hamanaka, Kazutoshi; Sekiguchi, Nodoka; Koizumi, Tomonobu
Abstract : Herein, we report a case of an angiosarcoma in a mediastinal non‐seminomatous germ cell tumor that exhibited growing teratoma syndrome during chemotherapy. A 26‐year‐old man presented with a giant anterior mediastinal mass, which was diagnosed as a non‐seminomatous germ cell tumor. The patient was administered three cycles of chemotherapy (bleomycin, etoposide, and cisplatin), but the mass grew despite normalization of tumor markers. Massive bleeding during thoracic surgery resulted in incomplete resection, and the mass was clinically and pathologically diagnosed as growing teratoma syndrome (only mature teratoma). The residual mass continued to grow, and complete resection was subsequently achieved after a detailed analysis of its vascular anatomy using angiography. The final pathological findings revealed angiosarcoma, which indicated a rare somatic type of mediastinal non‐seminomatous germ cell tumor.